2022
DOI: 10.1292/jvms.21-0349
|View full text |Cite
|
Sign up to set email alerts
|

Post mortem computed tomography as a complementary tool for diagnosing cholangiohepatitis in a giant panda (<i>Ailuropoda melanoleuca</i>)

Abstract: Post mortem computed tomography as a complementary tool for diagnosing cholangiohepatitis in a giant panda (Ailuropoda melanoleuca

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…In veterinary medicine, the cause of death has been determined through solely pathological analysis. While scientific studies in the field of human medicine have suggested the usefulness of postmortem diagnostic imaging, known as autopsy imaging (Ai) [ 14 ], only a few Ai case reports, such as for endangered animal species or zoo animals, have been reported in veterinary medicine [ 7 , 10 , 19 ]. Furthermore, literature on the use of imaging modalities for the purpose of veterinary forensics has currently been scant [ 17 , 18 ].…”
mentioning
confidence: 99%
“…In veterinary medicine, the cause of death has been determined through solely pathological analysis. While scientific studies in the field of human medicine have suggested the usefulness of postmortem diagnostic imaging, known as autopsy imaging (Ai) [ 14 ], only a few Ai case reports, such as for endangered animal species or zoo animals, have been reported in veterinary medicine [ 7 , 10 , 19 ]. Furthermore, literature on the use of imaging modalities for the purpose of veterinary forensics has currently been scant [ 17 , 18 ].…”
mentioning
confidence: 99%